[PP.19.23] LACK OF AN ASSOCIATION BETWEEN LOW PLASMA VITAMIN D AND CAROTID ARTERY STIFFNESS IN HYPERTENSION. (September 2017) - Catena, C.; Colussi, Gl.; Novello, M.; Martinis, F.; Sechi, L.A.
Abstract : Objective: Recent studies suggest an association between vitamin D deficiency and prevalence of cardiovascular disease in the general population. However, the evidence of a relationship between vitamin D status and vascular functional changes in hypertension is currently controversial. We aimed to investigate if the presence of low serum vitamin D levels is associated with an increased arterial stiffness in essential hypertension. Design and method: In 151 essential hypertensive patients (53 ± 13 y, 71 males) we measured serum 25 (OH)-vitamin D levels and performed a carotid ultrasound examination to determine variables of carotid stiffness, such as distensibility, compliance, Young elastic module and beta-stiffness. Furthermore, in a subgroup of 86 subjects we evaluated the augmentation index and the pulse wave velocity. The patients were subdivided into two groups according to the 25 (OH)-vitamin D levels, lower or higher than 30 nmol/L Results: A plasma vitamin D level lower than 30 nmol/L was found in 83 (55%) of 151 patients. Patients with low vitamin D levels were significantly older than those with a normal value of serum vitamin D. No significant differences in carotid artery distensibility, compliance, Young elastic modulus, and beta-stiffness were observed between patients with plasma vitamin D below or above 30 nmol/L. Also, the augmentation index and the pulse wave velocity were comparable in hypertensive patients with lower or higher plasma vitamin D levels. Conclusions: This study does not support the hypothesis of an association between vitamin D deficiency and functional vascular changes in hypertensive patients.